Investigation of Chromium Complexes with a Series of Tripodal Ligands1. Issue 12 (15th August 2013) - Schäfer, Sabrina; Becker, Jonathan; Beitat, Alexander; Würtele, Christian
Abstract A series of chromium(II) complexes containing the tripodal ligands tmpa, Me2uns‐penp, Me4apme and Me6tren were prepared and investigated with regard to their reactivity towards dioxygen. It was possible to structurally characterize the complexes [Cr(Me2uns‐penp)Cl]2(BPh4)2, [Cr(Me6tren)Cl]Cl, [Cr(Me4apme)Cl]BPh4 and [Cr(Me4ampe)Cl3]. The complexes show reactions with dioxygen, but it was not possible to characterize intermediates of these reactions. The oxidation behavior of the complexes towards organic substrates like toluene was investigated and oxidation of toluene to benzaldehyde was observed.